KARAKTERISTIK PASIEN TUBERKULOSIS TULANG BELAKANG DI RSUD DR. SOETOMO SURABAYA - Amy Rosalie Sukamto; Primadenny Ariesa Airlangga; Tri Hartini Yuliawati (Majalah Biomorfologi, 2019)
Background: Spine tuberculosis or spondylitis TB is one of the most common found extrapulmonary form of Mycobacterium tuberculosis infection that can be rapidly transmitted. However, people’s alertness are still to be increased and this disease is still rarely investigated. Objective: To study the characteristics of spondylitis tuberculosis patients to enhance the understanding of the disease and improve alertness to its signs and symptoms. Material and method: This study was conducted by assessing patients’ medical records based on particularly the epidemiology, signs and symptoms, radiology and laboratory tests. Collected data were assessed retrospectively and analyzed descriptively. Results: Of 35 patients, most come from early adult age group which is ranged from 26 to 35 years old (25.72%), and 57.14% of the patients were female. Sorted from the most to least common found signs and symptoms are back pain (85.71%), formation of abscess (74.29%), formation of gibbus (54.29%), fever (37.14%), and significant weight loss (34.29%). In radiologic evaluation, spine destruction were found on 82.86% of the patients. Erythrocyte sedimentation rate (ESR) was evaluated from 30 patients, 90% of which had increased ESR to >30 mm/hour. The leukocyte count was based from 35 patients, which result was 71.43% of them had normal count. Conclusions: Spondylitis TB is mostly found in adult females with back pain as the most common symptom. Most patients had spine destruction. Largely had elevated ESR while their leukocyte count mostly remains within normal range.